Work readiness dynamics of extended open-face sandwich generation college students in Malang - Nanda Alifia Kuswandari; Nur Eva (University of Merdeka Malang, 2025)
The extended open-face sandwich generation is a type of sandwich generation that grows at a massive rate. This phenomenon could affect one’s physical, mental, and financial condition, which leads to their work readiness. Work readiness refers to the extent to which an individual is ready to implement their attributes, competencies, and knowledge in their chosen career path. This research aims to analyze the dynamics and the cultural impact of Malang’s environment on the extended open-face sandwich generation college student’s work readiness building. This is qualitative research with a case study approach, using semi-structured interviews and analyzed through thematic analysis. The research results consist of six themes, such as the individual’s background and experiences, the cultural impacts of Malang’s environment, and four other themes regarding their work readiness, such as personal characteristics, organizational acumen, work competencies, and social intelligence. There are unique dynamics from each participant that are relevant to each other, with three of four participants having acquired the work readiness characteristics, while one participant needs to develop some characteristics.